INNOVATIVE TECHNOLOGIES AS A FACTOR OF FORMING A HEALTHY LIFESTYLE OF YOUTH STUDENTS IN PHYSICAL EDUCATION CLASSES (Physical Culture and Sport: Scientific Perspective, 2024)
This article is devoted to the study of the role of innovative technologies in the formation of a healthy lifestyle among students in physical education classes. Innovative technologies, such as virtual reality, mobile applications, wearable devices and interactive systems, provide unique opportunities for improving the educational process and increasing students' interest in physical education.The article analyzes the advantages of information technologies in teaching physical exercises, sports games and training, as well as their impact on motivation and effectiveness of classes. In addition, the possibilities of information technologies in keeping statistics, monitoring physical health, and developing individual training programs are explored, including the use of mobile applications, web resources, video materials, interactive games, and virtual reality.The article highlights the prospects for the further development of information technologies in physical culture and their impact on a healthy lifestyle in modern society.These technologies make it possible to create a powerful interactive, exciting and personalized learning environment that promotes more active involvement of students in physical activity and the formation of a healthy lifestyle. The article examines various aspects of the use of innovative technologies in physical education classes and their impact on the motivation of students to engage in sports, improving physical health and general well-being.In addition, the possibilities of information technologies in keeping records and analyzing the results of physical exercises, developing individual training programs and interaction between the teacher and students are highlighted.Based on the analysis of current research and the practical experience of teachers and trainers in the field of physical culture, the article highlights the prospects for the further development of the use of information technologies in this area and their impact on the healthy lifestyle of students.
Keywords: innovative technologies; physical culture; health